2011
DOI: 10.1007/s11663-011-9589-z
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Viscosities of CaO-MgO-FeO-MnO-SiO2 Molten Slags

Abstract: A model for estimating the viscosity of silicate melts is proposed in this article. The structural characteristics of a silicate slag can be described by the numbers of the bridging oxygen, nonbridging oxygen, and free oxygen present in the slag. A method of calculating the numbers of the different types of oxygen ions is presented in this article, which involves a simple approximation of ''complete bridge breaking.'' With just a few parameters, the model provides both the temperature and composition dependenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(41 citation statements)
references
References 37 publications
0
41
0
Order By: Relevance
“…Therefore, viscosity increases with increasing content of K 2 O. The viscosity model developed in our previous papers [3][4][5][6] will be used to estimate the viscosity of the compositions studied in this work and compare with the measured values. The detailed descriptions of the model can be found in the early publication, and only a brief introduction about the application to CaO-SiO 2 -Al 2 O 3 -K 2 O system will be given.…”
Section: B Effect Of K 2 O On Viscositymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, viscosity increases with increasing content of K 2 O. The viscosity model developed in our previous papers [3][4][5][6] will be used to estimate the viscosity of the compositions studied in this work and compare with the measured values. The detailed descriptions of the model can be found in the early publication, and only a brief introduction about the application to CaO-SiO 2 -Al 2 O 3 -K 2 O system will be given.…”
Section: B Effect Of K 2 O On Viscositymentioning
confidence: 99%
“…Furthermore, the measured viscosity data are compared with the estimated values calculated by the viscosity model proposed in our previous paper. [3][4][5][6] …”
Section: Introductionmentioning
confidence: 99%
“…It is closely related to the mass transfer velocity in the slag which determines the reaction kinetics, as well as the effectively separation of slag and metal, etc. Lots of experimental 1,2) and theoretical studies [3][4][5] have been done to investigate the viscosity variation regularity of fully liquid slags. However, in many pyrometallurgical processes, there are always suspension systems composed of liquid slags and insoluble solid particles, for instance, liquid blast furnace slag containing TiC solid particle during the smelting of titanium bearing ore; convert slags containing CaO and 2CaO·SiO 2 solid particles; copper slags containing solid magnetite (Fe 3 O 4 ) during the copper smelting if the atmosphere becomes too oxidized at the operating temperature.…”
Section: Introductionmentioning
confidence: 99%
“…5,6) Thus, viscosities of various slags have been measured by steelmakers, [7][8][9][10][11][12][13] and many researchers have also tried to predict the viscosity by different modeling. 5,[14][15][16] It has been found that the structure of silicate melts is the dominant factor which influences the physicochemical properties of high temperature slag according to the research of the structures of the silicate slags using the Fourier Transform Infrared (FT-IR) spectroscopy and Raman spectrum. 12,13,[17][18][19] Similarly, structure and properties of slags containing TiO2 have also been investigated by steelmakers in order to understand the relationship between structure and property.…”
Section: Introductionmentioning
confidence: 99%